2015
DOI: 10.4103/2230-8598.151257
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and reporting status for attempted Suicide: A hospital-based study

Abstract: Context: Suicide is a major public health problem and ranks second among the leading causes of death in both genders in 15-34 years. Suicidal attempts are 20 times higher than the completed suicides. Aims: The aim was to identify background risk factors and precipitating factors for suicide attempts in Pondicherry district and to fi nd out the reporting status of suicide attempts. Settings and Design: Hospital-based descriptive study. Subjects and Methods: 200 subjects who have attempted suicide from JIPMER an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…13 In contrast to our findings, studies in India by Singh A, Lingeswaran A, and Purushothaman P found more number of females attempting suicide, which could be due to differences in the population sampled. 17,19,20 In accordance with the results of a qualitative study on attempted suicide among young people in India, the majority of our subjects who attempted suicide were unmarried. 21 Low educational attainment, low socioeconomic status, and involvement in the agricultural sector were found to be the vulnerable demographics for heightened suicide risk in our sample.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…13 In contrast to our findings, studies in India by Singh A, Lingeswaran A, and Purushothaman P found more number of females attempting suicide, which could be due to differences in the population sampled. 17,19,20 In accordance with the results of a qualitative study on attempted suicide among young people in India, the majority of our subjects who attempted suicide were unmarried. 21 Low educational attainment, low socioeconomic status, and involvement in the agricultural sector were found to be the vulnerable demographics for heightened suicide risk in our sample.…”
Section: Discussionsupporting
confidence: 86%
“…17 Furthermore, gender disparities were evident in our study with the majority of those who attempted suicide being males, which is in line with the studies by Benjamin RN et al and Patel NS et al with males comprising a significant majority of suicide attempters 12,18. …”
supporting
confidence: 91%
“…13 Moreover young people who are more impulsive and less experienced with critical life situations often opt to attempt suicide to tide over difficult life situations. 14 Compared to completed suicides, attempted suicides are more common and it seems that the patients who attempt suicides are suffering from various psychiatric disorders. 15 Kashmir is a conflict zone and has been constantly under stress for the past 20 years which has led to rise in mental illnesses in the valley as reported by many studies conducted by various researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Male suicide rate is higher than the rate of female suicide in many countries (Jayasinghe and Foster, 2011;Poorolajal et al, 2015;Purushothaman et al, 2015: WHO, 2014b. In Sri Lanka, the rate of male suicide is *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%